Low-energy exciton pocket at finite momentum in tetracene molecular solids. (17th November 2015) - Roth, Friedrich; Nohr, Markus; Hampel, Silke; Knupfer, Martin
Abstract: The excited state dynamics in organic semiconductors plays an important role for many processes associated with light absorption and emission. We have studied the momentum dependence of the lowest singlet excitons in tetracene molecular solids, an archetype system for other organic semiconductors. Our results reveal an anisotropic band structure of these excitons with an energy minimum at finite momentum, i.e., a low-energy exciton pocket. The existence of such low-energy states might have important consequences for the photophysical behavior, also in view of applications in, e.g., organic solar cells. Our studies stress the importance of momentum-dependent considerations in organic systems.